Assessing extreme enantiomeric purity of (+)-1-(9-Fluorenyl)ethyl chloroformate by normal- and reversed-phase enantioselective chromatography: toward greener analytical strategies - Simone Manetto; Giulia Mazzoccanti; Elena Tuzi; Fabrizio Giorgi; Cristina di Giovanni; Michela Forte; Alessia Ciogli; Francesco Gasparrini (Analytica Chimica Acta, 2026)

The Italian effort toward a coordinated observation of Essential Variables (EOV, ECV, EBV) in European Marine Environments. Long-term observation in the central Mediterranean seas and Italian coasts - Simone Toller; Emilio Urbinati; Debora Bellafiore; Caterina Bergami; Francesca De Pascalis; Marcello G. Magaldi; Marco Bellacicco; Federico Bellati; Maristella Berta; Angelo Boccacci; Roberto Bozzano; Fabio Brunetti; et al. (Frontiers in Marine Science, 2026)
Monitoring Essential Ocean, Climate, and Biodiversity Variables (EOVs, ECVs and EBVs) collected through the marine Research Infrastructures (RIs) is critical for assessing environmental status, improving scientific knowledge and defining environmental policies. This study evaluates the capacity of the Italian marine monitoring system, including facilities such as fixed stations, buoys, autonomous platforms, and mobile systems across the Mediterranean Sea, to produce those variables. Conducted in 2023 within the framework of the ITINERIS project ( https://itineris.cnr.it/ ), which aims to strengthen coordination among national and ESFRI RIs (European Strategy Forum on Research Infrastructures), the analysis systematically examines the spatial, thematic, and technological coverage of EOVs, ECVs, EBVs observations and their alignment with international standards for environmental monitoring of 155 facilities from eight Italian and pan-European marine RIs. Of the 107 EVs recognized, 50% were actively produced by the RIs considered, with over 90% meeting the established requirements for EVs. These numbers will be updated to reflect the new equipment acquired during the project’s implementation up to early 2026, which is expected to boost EVs production by approximately 38-40%. The national monitoring network demonstrates a high degree of maturity for oceanic and climate variables, while biodiversity observations remain less represented, indicating the need for further technological innovation and automation. These findings emphasize the importance of enhancing coordination and harmonization among RIs to ensure balanced and interoperable monitoring. The study provides key recommendations to strengthen Italy’s capacity to contribute to the global characterization of EOVs, ECVs, and EBVs and to support evidence-based environmental assessments and the development of robust environmental management strategies at European level.

Food Safety and quality of some Italian honey: Study of long-persistent contaminants (heavy metals and PFAS) in different production areas in southern Italy - Sergio Passarella; Simone Moretti; Alessia Iannone; Fabiana Carriera; Sonia Ganassi; Dalila Di Criscio; Loretta De Giorgi; Giulia Corazzi; Ivan Notardonato; Carolina Barola; Roberta Galarini; Pasquale Avino; et al. (Food Chemistry, 2026)

Prenatal exposure to fine particulate matter PM2.5 and small for gestational age: a Bayesian model for area-based data in Milan - Simone Colombara; Rossella Murtas; Sara Tunesi; Alessandra Guglielmi; Antonio Giampiero Russo; Paola Angelini; Serena Broccoli; Marco Monti; Nicola Caranci; Katia Raffaelli; Daniela Fortuna; Paolo Giorgi Rossi; et al. (Environmental and Ecological Statistics, 2025)

Association between long-term exposure to air pollution and cause-specific mortality within five Italian longitudinal metropolitan studies - Federica Nobile; Nicola Caranci; Elena Strippoli; Valentina Adorno; Alessandra Allotta; Lucia Bisceglia; Ida Galise; Claudio Gariazzo; Sara Maio; Paola Michelozzi; Walter Pollina Addario; Andrea Ranzi; et al. (Atmospheric Environment, 2024)

Recreating Leber’s Hereditary Optic Neuropathy in iPS derived Neurons: Shedding Light on Pathogenic Mechanisms to Combat Blindness - Camille Peron; Alessandra Maresca; Andrea Cavaliere; Angelo Iannielli; Chiara Fasano; Ivano Di Meo; Alberto Danese; Simone Patergnani; Danara Ormanbekova; Carlotta Giorgi; Paolo Pinton; Vania Broccoli; et al. (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

Association between short-term exposure to air pollutants and cause-specific daily mortality in Italy. A nationwide analysis - Claudio Gariazzo; Matteo Renzi; Alessandro Marinaccio; Paola Michelozzi; Stefania Massari; Camillo Silibello; Giuseppe Carlino; Paolo Giorgi Rossi; Sara Maio; Giovanni Viegi; Massimo Stafoggia; Sandra Baldacci; et al. (Environmental Research, 2023)

Ocean Energy Systems Wave Energy Modelling Task: Modelling, Verification and Validation of Wave Energy Converters - Fabian Wendt; Kim Nielsen; Yi-Hsiang Yu; Harry Bingham; Claes Eskilsson; Morten Kramer; Aurélien Babarit; Tim Bunnik; Ronan Costello; Sarah Crowley; Benjamin Gendron; Giuseppe Giorgi; et al. (Journal of Marine Science and Engineering, 2019)
The International Energy Agency Technology Collaboration Programme for Ocean Energy Systems (OES) initiated the OES Wave Energy Conversion Modelling Task, which focused on the verification and validation of numerical models for simulating wave energy converters (WECs). The long-term goal is to assess the accuracy of and establish confidence in the use of numerical models used in design as well as power performance assessment of WECs. To establish this confidence, the authors used different existing computational modelling tools to simulate given tasks to identify uncertainties related to simulation methodologies: (i) linear potential flow methods; (ii) weakly nonlinear Froude–Krylov methods; and (iii) fully nonlinear methods (fully nonlinear potential flow and Navier–Stokes models). This article summarizes the code-to-code task and code-to-experiment task that have been performed so far in this project, with a focus on investigating the impact of different levels of nonlinearities in the numerical models. Two different WECs were studied and simulated. The first was a heaving semi-submerged sphere, where free-decay tests and both regular and irregular wave cases were investigated in a code-to-code comparison. The second case was a heaving float corresponding to a physical model tested in a wave tank. We considered radiation, diffraction, and regular wave cases and compared quantities, such as the WEC motion, power output and hydrodynamic loading.

Using a multi-method approach based on soil radon deficit, resistivity, and induced polarization measurements to monitor non-aqueous phase liquid contamination in two study areas in Italy and India - Mauro Castelluccio; Sudha Agrahari; Gabriele De Simone; Francesca Pompilj; Carlo Lucchetti; Debashish Sengupta; Gianfranco Galli; Pierluigi Friello; Pierpaolo Curatolo; Riccardo Giorgi; Paola Tuccimei (Environmental Science and Pollution Research, 2018)

Spatial variability in distribution and prevalence of skeletal eroding band and brown band disease in Faafu Atoll, Maldives - Simone Montano; Aurora Giorgi; Matteo Monti; Davide Seveso; Paolo Galli (Biodiversity and Conservation, 2016)

Entoprocta–sponge associations in the Indian Ocean - Aurora Giorgi; Matteo Monti; Paolo Galli; Simone Montano (Coral Reefs, 2016)

ATP synthesis and storage - Massimo Bonora; Simone Patergnani; Alessandro Rimessi; Elena De Marchi; Jan M. Suski; Angela Bononi; Carlotta Giorgi; Saverio Marchi; Sonia Missiroli; Federica Poletti; Mariusz R. Wieckowski; Paolo Pinton (Purinergic Signalling, 2012)

Genotoxic and mono-oxygenase system effects of the fungicide maneb - Simone Bertini; Renata Del Carratore; Mario Giorgi; Giorgio Bronzetti; Clara Della Croce (Archives of Toxicology, 2000)